Exploring APOE genotype effects on Alzheimer's disease risk and amyloid β burden in individuals with subjective cognitive decline: The FundacioACE Healthy Brain Initiative (FACEHBI) study baseline results. Issue 5 (20th November 2017) - Moreno–Grau, Sonia; Rodríguez‐Gómez, Octavio; Sanabria, Ángela; Pérez‐Cordón, Alba; Sánchez‐Ruiz, Domingo; Abdelnour, Carla; Valero, Sergi; Hernández, Isabel; Rosende‐Roca, Maitée; Mauleón, Ana; Vargas, Liliana; Lafuente, Asunción; et al.
Abstract: Introduction: Subjective cognitive decline (SCD) has been proposed as a potential preclinical stage of Alzheimer's disease (AD). Nevertheless, the genetic and biomarker profiles of SCD individuals remain mostly unexplored. Methods: We evaluated apolipoprotein E ( APOE ) ε4's effect in the risk of presenting SCD, using the Fundacio ACE Healthy Brain Initiative (FACEHBI) SCD cohort and Spanish controls, and performed a meta‐analysis addressing the same question. We assessed the relationship between APOE dosage and brain amyloid burden in the FACEHBI SCD and Alzheimer's Disease Neuroimaging Initiative cohorts. Results: Analysis of the FACEHBI cohort and the meta‐analysis demonstrated SCD individuals presented higher allelic frequencies of APOE ε4 with respect to controls. APOE dosage explained 9% (FACEHBI cohort) and 11% (FACEHBI and Alzheimer's Disease Neuroimaging Initiative cohorts) of the variance of cerebral amyloid levels. Discussion: The FACEHBI sample presents APOE ε4 enrichment, suggesting that a pool of AD patients is nested in our sample. Cerebral amyloid levels are partially explained by the APOE allele dosage, suggesting that other genetic or epigenetic factors are involved in this AD endophenotype. Highlights: The FACEHBI sample presents APOE ε4 enrichment, suggesting it contains a pool of AD patients. APOE ε4 is a risk factor of being diagnosed with SCD. APOE ε4 only explains ≈10% of brain amyloid burden variability in SCD. The relationship between APOE and brain amyloid burden across clinical diagnoses highlights the importance of adjusting for clinical status when conducting GWAS of cerebral Aβ levels.